Analysis of Green Product Implementaion in Sudamala Resort Komodo - Umul, Dewi Sartika; Antariksa Berybe, Gregorius; Nail, Maria; Etheldreda Ine Dae , Yohana (Centre for Tourism Studies and Journal Publication of Sekolah Tinggi Pariwisata Mataram, 2023)
The utilization of green products in hotel operations is one of the principles of sustainable tourism. One of the five-star hotels that implement green products in Labuan Bajo is Sudamala Resort Komodo. This research aims to find out the role of the Sudamala Hotel in implementing a Sustainable program through Green Products. This research is qualitative. Data was collected using interviews, observation, documentation, and literature study. The respondents were Human Resource Manager (HRM), Food and Beverage Manager (FBM), executive housekeeping, and department employees at Sudamala Resort Komodo. The data analysis technique used was the Miles and Huberman (1992). The results of this research show that the Sudamala Resort Komodo Hotel has implemented green products. The utilization of green products at the Sudamala Resort Komodo Hotel has been implemented based on the criteria of ASEAN. Green Hotel Standard, namely the utilization of local products and the utilization of environmentally friendly products. The implementation of green products at the Sudamala Resort Komodo Hotel has been carried out consistently and sustainably to date. Apart from that, in implementing green products there are still several things that become obstacles both in using local products and in using environmentally friendly products.